Changes and relationship of N6-methyladenosine modification and long non-coding RNAs in oxidative damage induced by cadmium in pancreatic β-cells. (1st June 2021) - Qu, Tengjiao; Mou, Yahao; Dai, Jiao; Zhang, Xiaoli; Li, Mengzhu; Gu, Shiyan; He, Zuoshun
Highlights: m 6 A-modified LncRNAs and m 6 A are changed in CdSO4 -induced oxidative damage. A positive relationship was observed between m 6 A-modified LncRNAs and m 6 A. m 6 A modification may be co-regulated by METTL3 and FTO in cadmium-treated cells. Abstract: N 6 -methyladenosine (m 6 A) modification and m 6 A-modified Long non-coding RNAs (LncRNAs) play crucial roles in various pathological processes, yet their changes and relationship in cadmium-induced oxidative damage are largely unknown. Here, five m 6 A-modified LncRNAs (LncRNA-TUG1, LncRNA-PVT1, LncRNA-MALAT1, LncRNA-XIST, LncRNA-NEAT1), which have been evidenced to involve in oxidative damage, were selected and their binding proteins were submitted to bioinformatics analysis. Our analysis results showed that these five m 6 A-modified LncRNAs bound to different regulatory proteins of m 6 A modification, implicating that m 6 A modification on LncRNAs may synergistically control by multiple regulatory proteins. Furthermore, the detection data revealed that levels of m 6 A modification, methyltransferase-like 3 (METTL3) and fat mass and obesity-associated protein (FTO) were all significantly decreased in CdSO4 -induced oxidative damage, which was demonstrated by increasing ROS accumulation and MDA contents as well as decreasing SOD activities. More importantly, LncRNA-MALAT1 and LncRNA-PVT1 indicated downward trend and showed positive relationship with m 6 A modification. Collectively, our results showed that m 6 A modification and m 6 A-modified LncRNAs may involve in oxidative damage induced by cadmium.